2020
DOI: 10.30534/ijatcse/2020/88922020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of Task Scheduling Algorithms in Cloud Environments

Abstract: Task scheduling algorithms in cloud have come a long way, from simplistic algorithms like first come first serve, to bio-inspired & machine learning algorithms like Q-learning and genetic algorithms. The main objective of any task scheduling algorithm is to minimize the number of execution cycles needed to completely and effectively execute a given set of tasks. In this work, we present a comparison of different scheduling algorithms and their performance evaluation. The proposed research takes into considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They checked all the algorithms in various tasks and under various patterns of the virtual machine ( VM) in the study. According to the report, machine learning-based algorithms work better than others in terms of general load balancing performance [36].…”
Section: Related Workmentioning
confidence: 99%
“…They checked all the algorithms in various tasks and under various patterns of the virtual machine ( VM) in the study. According to the report, machine learning-based algorithms work better than others in terms of general load balancing performance [36].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, studies have found evidence that inefficient task scheduling in cloud computing can negatively impact performance efficiency and drastically increase resource use [5]. The suboptimal allocation of tasks using traditional scheduling strategies such as First Come First Served (FCFS), Round Robin (RR) and Shortest Job First (SJF) has proven insufficient for dynamic cloud environments [6].…”
Section: Introductionmentioning
confidence: 99%
“…As well, research works are widespread, where the formation of schedules is carried out on the basis of graph theory [9], genetic [10] and heuristic algorithms [11] with their subsequent implementation in software. However, existing computer scheduling programs based on existing models, focused on the conditions of specific production or have excessive versatility of the implementation of common functions [8], [12]- [15] and high market value and cannot be adapted to solve the problem of forces coordination during the operation.…”
Section: Introductionmentioning
confidence: 99%